European Energy Efficiency and Decarbonization Strategies Beyond 2030 A Sectoral Multi-model Decomposition - Hannah Förster; Katja Schumacher; Enrica De Cian; Michael Hübler; Ilkka Keppo; Silvana Mima; Ronald D. Sands (Fondazione Eni Enrico Mattei (FEEM), 2014)
Energy efficiency and decarbonization are important elements of climate change mitigation. We draw on European mitigation scenarios from the EMF28 modeling exercise to decompose economy-wide and sectoral emissions into their main components. We utilize the Logarithmic Mean Divisia Index (LMDI) to gain insights into five effects: affluence, energy intensity, carbon intensity, conversion efficiency, and structural change. Economy-wide analysis suggests that energy efficiency improvements (including end-use efficiency of economic production and structural change of the economy) determine emission reductions short to medium term while decarbonization becomes more important in the long run. Sectoral analysis suggests that electricity generation holds the largest potential for decarbonization. Mitigation in the transport and energy-intensive sectors is limited by technology availability, forcing output and energy inputs to decline to meet the given mitigation pathways. We conclude that energy efficiency improvements could bridge the time until carbon-free technologies mature, while their quick development remains essential.
Keywords: Q4; Q5; Q51; 330; Decomposition Analysis; Decarbonization; Model Intercomparison